2019
DOI: 10.1007/s11892-019-1194-6
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Beta Cell Identity in Type 1 and Type 2 Diabetes

Abstract: Purpose of Review To discuss the current understanding of “β cell identity” and factors underlying altered identity of pancreatic β cells in diabetes, especially in humans. Recent Findings Altered identity of β cells due to dedifferentiation and/or transdifferentiation has been proposed as a mechanism of loss of β cells in diabetes. In dedifferentiation, β cells do not undergo apoptosis; rather, they lose their identity and function. Dedifferentiation is well characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 123 publications
(164 reference statements)
5
90
1
7
Order By: Relevance
“…Ectopic expression of key TFs and hormones specific for other endocrine cell types [147] indicates the plasticity of β-cells to differentiate toward other endocrine cell types (Figure 3) [148]. Evidence of ectopic expression of other hormones in β-cells comes from a mouse model with impaired insulin secretion and glucose intolerance caused by the lack of Nkx2-2 (TF needed for maintaining mature β-cell identity).…”
Section: Diabetic Conditions: β-Cells Derailmentioning
confidence: 99%
“…Ectopic expression of key TFs and hormones specific for other endocrine cell types [147] indicates the plasticity of β-cells to differentiate toward other endocrine cell types (Figure 3) [148]. Evidence of ectopic expression of other hormones in β-cells comes from a mouse model with impaired insulin secretion and glucose intolerance caused by the lack of Nkx2-2 (TF needed for maintaining mature β-cell identity).…”
Section: Diabetic Conditions: β-Cells Derailmentioning
confidence: 99%
“…Furthermore, the number of Taf4-expressing BCs did not increase between 34 and 55 weeks arguing against proliferation of non-recombined BCs. Alternatively, Taf4-expressing BCs may arise from trans-differentiation of alpha cells or other islet populations into BCs as has been previously described, for example under conditions of reduced BC-mass [30][31][32][33] , one of the consequences of Taf4 inactivation. Notwithstanding the mechanisms involved, these data showed that despite reduced BC mass through increased apoptosis and an ensuing elevated glycaemia, the BC population was only partially and slowly replaced by newly generated BCs.…”
Section: Discussionmentioning
confidence: 89%
“…Bulk RNA-seq and ATAC-seq showed that Taf4 inactivation had a potent impact on BC trans-differentiation into alpha cells and vice versa has been described in diabetes, in genetically modified mice and after various pathological or chemical treatments. The molecular mechanisms involved particularly at the transcriptional level are however not fully understood 30,32,[45][46][47] . In type 2 diabetes, hyperglycaemia seems to induce BC dedifferentiation with diminished expression BC function genes and key BC transcription factors, but expression of BC forbidden genes and it may involve reversion to a Ngn3-expressing precursor state as a prerequisite to trans-differentiation to alpha or delta cells 33,40,48 .…”
Section: A Model For Beta Cell Trans-differentiationmentioning
confidence: 99%
“…Several studies in experimental hypothyroidism support this concept. In diabetes, hypothyroidism induces the dedifferentiation and/or transdifferentiation of pancreatic β -cells, and these phenomena (instead of apoptosis) have been proposed as putative explanations for pancreatic β -cell loss ( Moin and Butler, 2019 ). Notably, the simultaneous overexpression of TRα1 and the administration of T3 enhanced cell cycle progression and proliferation, leading to the reprogramming of pancreatic cells into insulin-producing cells, in both the rat β -cell line and in an animal model of STZ-induced diabetes ( Furuya et al, 2010 ).…”
Section: Thyroid Hormone Signalingmentioning
confidence: 99%